Towards Improved Traffic Impact Assessments for Construction Sites - Robert Hilbrich; Jürgen Besler; Natalie Dust; Heiner Kretzer; Bertram Monninkhoff (SUMO Conference Proceedings)
The coordination of construction sites in urban areas is increasingly critical to minimizing their traffic impact. Traditionally, traffic assessments were conducted late in the planning process, limiting opportunities for proactive mitigation. This paper presents a SUMO-based prototype that integrates the Baustellenatlas, a digital construction coordination tool, with SESAM, a cloud-based SUMO simulation service, via a REST API. The system enables automated traffic impact assessments, allowing users to modify road network properties and simulate their effects in real time. Two case studies in Berlin evaluated the prototype: a small-scale demonstrator at Molkenmarkt with randomly generated traffic and a larger, calibrated scenario at Tempelhofer Damm, reflecting real-world demand data. Results highlight the potential of integrating microscopic traffic simulation into early-stage construction planning, making data-driven assessments more accessible. Key challenges include the visualization of rerouting effects, long-term detour modeling, and expanding network modification capabilities. Future work will focus on public transport integration, adaptive signal control, and automatic scenario calibration using real-time traffic data.